MOTIVASI WISATAWAN BERKUNJUNG KE DESA WISATA GUMBRIH, PEKUTATAN, JEMBRANA - BALI - Gusti Ngurah Joko Adinegara; I Ketut Sirna; I W K Teja Sukmana (Universitas Merdeka Malang, 2020)
Tourism is expected to contribute to the economic growth in a region and tourism villages are a potential that is being developed by local governments, especially in Bali. Gumbrih Tourism Village has considerable potential in tourist attractions that are offered and has been established as a tourist village in 2017. The purpose of this study is to determine the factors that motivate tourists to visit Gumbrih Tourism Village. Factor analysis is used to provide the dimensions that underlie visiting motivation factors. The survey method was conducted and is expected to provide information for village tourism managers. From 98 respondents, it was found that from the eighteen variables used, four factors were formed that motivated tourists to visit the Gumbrih Tourism Village. These four factors are formed from the results of the analysis are the attractions offered, the uniqueness of local products, the ease of access and the protection of reptiles. All variables (% variance) used were able to illustrate the motivation of tourists by 75.72 percent. Knowing the main reasons tourists visit can help the tourist village manager meet the needs and desires of tourists, because tourists want to know something different and unique from the places they visit.